2013
DOI: 10.1021/ja3122334
|View full text |Cite
|
Sign up to set email alerts
|

Ordering a Dynamic Protein Via a Small-Molecule Stabilizer

Abstract: Like many coactivators, the GACKIX domain of the master coactivator CBP/p300 recognizes transcriptional activators of diverse sequence composition via dynamic binding surfaces. The conformational dynamics of GACKIX that underlie its function also render it especially challenging for structural characterization. We find that the ligand discovery strategy of Tethering is an effective method for identifying small molecule fragments that stabilize the GACKIX domain and enables, for the first time, the crystallogra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

5
79
0
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 82 publications
(85 citation statements)
references
References 34 publications
5
79
0
1
Order By: Relevance
“…Overall, we found that binding of MLL and/or c-Myb resulted in an increase in stability (or a reduction in dynamics) of the α 3 C terminus and the L 12 -G 2 loop. This is consistent with observations made in previous NMR and computational studies, which have led to the suggestion that the increased structural stability of KIX may play a role in allosteric signaling (4,20,(28)(29)(30)(31)(32). For example, NMR backbone order parameter measurements of KIX have demonstrated that the L 12 -G 2 loop and the C-terminal residues of the α 3 helix are more rigid when MLL is bound to KIX (29).…”
Section: Discussionsupporting
confidence: 90%
See 4 more Smart Citations
“…Overall, we found that binding of MLL and/or c-Myb resulted in an increase in stability (or a reduction in dynamics) of the α 3 C terminus and the L 12 -G 2 loop. This is consistent with observations made in previous NMR and computational studies, which have led to the suggestion that the increased structural stability of KIX may play a role in allosteric signaling (4,20,(28)(29)(30)(31)(32). For example, NMR backbone order parameter measurements of KIX have demonstrated that the L 12 -G 2 loop and the C-terminal residues of the α 3 helix are more rigid when MLL is bound to KIX (29).…”
Section: Discussionsupporting
confidence: 90%
“…Previous studies have observed changes in the KIX structure resulting from transcription factor binding, and both MLL and c-Myb have been shown to allosterically affect the affinity of KIX for the complementary peptide (4,20,(28)(29)(30)(31)(32). However, a connection between the changes in structural dynamics in KIX and how this directly leads to shifts in transcription factor binding affinities remain tenuous.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations